Long‐term interannual variability in larval dispersal and connectivity of the Norway lobster (Nephrops norvegicus) around Ireland: When supply‐side matters. (17th February 2022) - McGeady, Ryan; Lordan, Colm; Power, Anne Marie
Abstract: Dispersal of meroplankton larvae in the ocean is a key process which determines larval supply to areas of suitable habitat and enables connectivity between populations, particularly for nonmigratory species. Our objective was to use a biophysical larval transport model to create a time series (2000–2019) of larval retention, dispersal distance and connectivity estimates for the commercially important Norway lobster ( Nephrops norvegicus ) on mud grounds off Ireland. Where time series of population estimates were sufficiently long to conduct analysis, we also investigated if larval dispersal indices could be used to predict variations in adult density, after a lag period, hypothesising that this would only apply to grounds with consistently low larval supply. Grounds off Ireland had varying characteristics related to their ability to retain and exchange larvae which was influenced by the local hydrodynamic regime and spatial isolation from other grounds. Larval supply was consistently low on the Aran grounds to the west of Ireland, which have experienced abundance declines in the past. The time series of modelled larval dispersal indices at the Aran grounds was linked to empirical adult burrow densities with a 3‐year lag. Whereas the western Irish Sea, which has consistently high larval supply, showed no such relationship. Models can provide important larval recruitment information early in the life cycle for species of commercial or conservation importance.